THE ROLE OF THE GANGGANGPANJANG VILLAGE GOVERNMENT IN DEVELOPING THE PUNDEN MBAH RECO TOURIST ATTRACTION - Salsabila, Nindya Aura; Balahmar, Ahmad Riyadh Umar (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Study This aim For analyze role Gagangpanjang Village Government in develop Object Tour Punden Mbah Reco in the District Tanggulangin, Regency Sidoarjo. The study focused on four role indicators according to Siagian's theory: stabilizer, innovator, modernizer, and pioneer, to determine the extent to which village governments encourage community participation, optimize local potential, and ensure sustainable tourism development. Method: The research method used was descriptive qualitative with a case study approach. Data were collected through field observations, in-depth interviews with village officials, tourism managers, and MSMEs, as well as documentation related to the management of the Punden Mbah Reco tourist attraction. Informants were selected using a purposive sampling technique. Data analysis was carried out using the Miles and Huberman interactive model to identify patterns of village government roles according to Siagian's theory indicators. Results: The results of the study reveal concrete strategies of village governments in initiating capacity building programs, reactivating digital promotion, and exploring partnerships with external parties. Novelty: The novelty of this study lies in a comprehensive evaluation of the implementation of four indicators of village government roles in the context of community-based rural tourism development. This study shows how village leadership faces real obstacles such as limited supporting infrastructure, suboptimal digital promotion capacity, and the lack of intensive cooperation with the private sector. These findings make an important contribution to the understanding of village governance for sustainable tourism and offer a local tourism empowerment model that integrates community participation, digital transformation, and proactive leadership of village government.